Synthesis and solid-state structural characterization of bis (thiocyanatemercury)tetracarbonyliron - Mauro, A. E.; Santos, R. H A; Gambardella, M. T P; Francisco, R. H P (Elsevier, 1987)
The bis (thiocyanatemercury)tetracarbonyliron, [Fe(CO)4(HgSCN)2], was prepared from [Fe(CO) 5] and Hg(SCN)2, and studied by IR spectroscopy and X-ray diffraction. The compound crystallizes in the tetragonal space group I4,1/a. The unit cell, with dimensions of a = 13.778(3), c = 13.234(3) Å, V = 2512.3(9) Å3, contains four molecules. The iron atom is octahedrally coordinated by four carbonyl groups and two mercury atoms in cis positions. The coordination of the mercury atoms is distorted square-planar, since, besides mercury-iron and mercury-sulphur bonds, there are also mercury-mercury and mercury-nitrogen interactions. The FeHg distance is 2.506(5)Å and the HgFeHg angle is 78.0(1)°. © 1987.